Optimal assignment for tasks of available resources (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Assignment model is a way that contributes in achieving the perfect use of available resources, the goal of it is getting most profit or decreasing cost or time, many processes can be done such as (jobs, workers), in a way of distributing it to the available resources which only one process is specified to every type of facility (available resources like machines). In this research, there are two methods for solving the assignment model, by making questionnaire form for certain professors in the accounting deportment of  Al-Esraa university college, the assignment model has been solved by using two algorithms and the results are equal.